The impact of market orientation on new product performance through product launch quality: A resource-based view - Farbod Fakhreddin; Pantea Foroudi (Cogent Business & Management, 2022)
Grounded on the resource-based view, this study aims to examine the mediating role of product launch quality as a deployment mechanism in the association between market orientation and new product performance. Conducting an on-site survey of Iranian manufacturing industries, this study applies covariance-based structural equation modeling to test research hypotheses and verify the proposed theoretical model. The empirical findings indicate market orientation is a critical knowledge-based resource enhancing firms' product launch quality, and right decisions concerning the product launch elevate new product performance. The results also reveal while market orientation significantly impacts new product performance, product launch quality is a crucial deployment mechanism for leveraging market orientation as it fully mediates impacts of market orientation on new product performance. The current static characterization of the resource-based view signifies strategic resources have potential value, but unleashing this potential requires incorporation of deployment mechanisms in the resource-performance link. Besides, considering this insufficient view, prior studies have revealed mixed and inconsistent results. Accordingly, through examining product launch quality as a deployment mechanism for leveraging market orientation on new product performance, not only does this study address inconsistent findings, but it noticeably contributes to the resource-based view by casting light on the mechanism through which market orientation as a strategic knowledge-based resource leads to superior new product performance.
Keywords: 650; innovation management; market orientation; new product development; New product performance; product innovation; product launch quality; resource-based view